2016
DOI: 10.1371/journal.pone.0165232
|View full text |Cite
|
Sign up to set email alerts
|

Marked Body Shape Concerns in Female Patients Suffering from Eating Disorders: Relevance of a Clinical Sub-Group

Abstract: Concerns about body shape and weight are core diagnostic criteria for eating disorders although intensity varies between patients. Few studies have focused on the clinical differences relative to the intensity of these concerns. Nonetheless, they might have a prognostic value. This study was aimed at identifying the characteristics associated with marked body shape concerns in patients with an eating disorder. Data was collected from a systematic and standardized clinical assessment of outpatients seeking trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Perfectionism is “a personality disposition characterized by striving for flawlessness and setting exceedingly high standards of performance accompanied by overly critical evaluations of one’s behavior” [1]. It has given rise to interest growing in research, possibly due to the substantial evidence of its positive relation with psychopathology [2,3], acting as a factor of resistance to change and hindering the treatment efficacy of multiple disorders [4,5]. However, research on perfectionism during childhood and the adolescence is an incipient field [6], although it would provide knowledge about the situations that promote its maintenance and development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Perfectionism is “a personality disposition characterized by striving for flawlessness and setting exceedingly high standards of performance accompanied by overly critical evaluations of one’s behavior” [1]. It has given rise to interest growing in research, possibly due to the substantial evidence of its positive relation with psychopathology [2,3], acting as a factor of resistance to change and hindering the treatment efficacy of multiple disorders [4,5]. However, research on perfectionism during childhood and the adolescence is an incipient field [6], although it would provide knowledge about the situations that promote its maintenance and development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[333435] Negative body image is unswervingly related to low self-esteem which further contribute to the trailing weight loss strategies and development of eating disorders. [36] Wrong perception of body image is a significant barrier for any behavioral change amongst the students because unless student nurses identify their weight as a consequence of the improper nutrition and lifestyle, it is less likely to motivate them and take preventive and curative measures. Although latest studies have proved that less calorie intake may not be helpful in losing weight,[37] nevertheless due to inadequate knowledge, these habits are followed consistently.…”
Section: Discussionmentioning
confidence: 99%
“…The blogger criticized the findings of two studies in which the evidence of the absence of BID was not considered to be a lack of BID evidence, but evidence of patient denial. In the first case the study by Gailledrat et al ( 148 ) reported, “ a significant proportion of patients seeking treatment for ED had no or only mild concerns with body shape. This could be of surprise as body shape concerns are core symptoms of ED ” (p. 7).…”
Section: The Role Of the Bid Construct In The Acculturation And Indocmentioning
confidence: 99%